Perlindungan Hukum Terhadap Notaris dalam Proses Penyidikan Perkara Pidana Terkait Akta Otentik (Studi Kasus Putusan Pengadilan Tata Usaha Negara Tanjungpinang Nomor 13/G/2018/PTUN-TPI) - Suzeta, Berliana; Ismansyah, Ismansyah; Yasniwati, Yasniwati (Universitas Ekasakti, 2023)
In Carrying out his position, a Notary has the potential to be involved in legal cases, including criminal law cases, which result in him having to be examined by investigators, public prosecutors and judges. Based on Article 66 paragraph (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the position of Notary, the examination of a Notary is carried out with the approval of the Notary honorary council. Basically this approval is necessary because to protect the Notary from breaches of disclosing the secret of the deed and to protect the Notary’s own deed so that it remains confidential. To review and analyze this research, the authors used the statutory approach and the conceptual approach. The results of the study show that the rules for summoning a Notary by an investigator are related to a Notary deed that has an indication of a criminal act regulated in Article 66 paragraph (1) of Law Number 2 of 2014 and Permenkumham Number 17 of 2021. Notary summons by an investigator must have the approval of the assembly honorary regional Notary. The procedures are: First, the investigator submits a letter of request for summons of a Notary to the regional Notary honorary council; Second, the regional Notary honorary council forms the examining council; Third, the examining council conducts an examination of the Notary; Fourth, the examining council submits a report to the head of the regional Notary honorary council; Fifth, the regional Notary honorary council provides answers regarding giving approval or refusing. Notaries in providing legal services to the public need to get legal protection and guarantees from the state, in this case through the regional Notary honorary council. The legal protection in question is that investigators may not immediately summon or examine a Notary, without prior approval from the regional Notary honorary council. If the investigator commits the violation, then the investigator’s actions can be categorized as an act that violates the law, so that the summons or examination carried out by the investigator has been procedurally flawed.